То the centenary anniversary of the birthday of Professor Mykhailo Pavlovych Lysytsya - Valakh, M.Ya. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2021)
Professor Mykhailo Pavlovych Lisitsa is one of the outstanding physicists whose works have made a considerable contribution to the fundamentals of modern optics and spectroscopy of semiconductors and dielectrics.